(untitled) (England, 1999)
This book contains state-of-the-art commentaries on all these aspects of the intestinal microflora and probiotics and provides an authoritative review of important aspects of probiotic research. Written by leading experts in the field, each chapter affords a critical insight to a particular topic, reviews current research, discusses future direction and aims to stimulate discussion. An essential text for all microbiologists, health professionals, biotechnologists, dairy and food scientists.
Keywords: Bacteria,Probiotics,Vi khuẩn; Health aspects,Khía cạnh sức khỏe